2020
DOI: 10.1002/arch.21679
|View full text |Cite
|
Sign up to set email alerts
|

Orally delivered dsRNA induces knockdown of target genes and mortality in the Asian long‐horned beetle, Anoplophora glabripennis

Abstract: The Asian long-horned beetle (ALB) Anoplophora glabripennis is a serious invasive forest pest in several countries, including the United States. Methods available to manage or eradicate this pest are extremely limited, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The only cerambycid to be examined for dietary RNAi susceptibility is Asain long-horned beetle ( Anoplophora glabripennis ). Dhandapani et al (2020a) exposed A. glabripennis larvae to dietary dsRNA ( in vitro synthesized) in sucrose solution for 3 days, and mortality was monitored up to 10 days. The authors observed (depending on target gene) 17–25%, 50–67%, and 75–90% larval mortality associated with force-fed doses of 2, 5, and 10 μg dsRNA/day, respectively.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“…The only cerambycid to be examined for dietary RNAi susceptibility is Asain long-horned beetle ( Anoplophora glabripennis ). Dhandapani et al (2020a) exposed A. glabripennis larvae to dietary dsRNA ( in vitro synthesized) in sucrose solution for 3 days, and mortality was monitored up to 10 days. The authors observed (depending on target gene) 17–25%, 50–67%, and 75–90% larval mortality associated with force-fed doses of 2, 5, and 10 μg dsRNA/day, respectively.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“…Due to the high specificity and efficiency of RNAi, more and more research groups tried to develop new pest control methods based on this technology and the latest research results showed that inhibiting the expression of important genes in the growth and development process of insects could cause growth and development disorders or death of insects. Many relevant target genes were screened, such as the inhibitor of apoptosis (IAP), vacuolar sorting protein SNF7 (SNF7), and snakeskin (SSK) of Anoplophora glabripennis (Dhandapani et al, 2020); the chitinase (Sf-CHI), chitin synthase B (Sf-CHSB), sugar transporter SWEET1 (Sf-ST), and hemolin (Sf-HEM) of Spodoptera frugiperda (Wan et al, 2021); the leucine-rich repeat-containing (LGR2) of Hyphantria cunea (Sun et al, 2021) and so on. All of above is the strong evidence that RNAi can be used as a new method for pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Anoplophora glabripennis (Coleoptera: Cerambycidae) (Asian long-horned beetle, ALB) is an important wood-boring pest of poplar, willow, acer, elm, buckeye and birch trees (Faccoli & Favaro, 2016;Gao & Li, 2001;Gao et al, 2000Gao et al, , 2009Haack et al, 2010;Tang et al, 1996). The larvae tunnel into the host wood and infested trees is highly susceptible to wind damage, reducing their economic and ecological value (Dhandapani et al, 2020;Gao & Li, 2001). During the mid-to late twentieth-century ALB caused serious economic and ecological damage to poplar shelterbelts in northwestern China (Luo et al, 2002;Lv et al, 2004), and even today, it remains a major problem on Salix, Ulmus and Populus species in Inner Mongolia Autonomous Region, Gansu Province and Xinjiang Uygur Autonomous Region (Golec et al, 2018;Wang et al, 2016;Yue et al, 2011).…”
mentioning
confidence: 99%
“…Since it was found in North America in the late 1990s, ALB has been listed as an important quarantine forest pest globally (Haack et al, 2010). Because it is very difficult to control, it continues to pose a significant risk to deciduous hardwood tree species around the world (Dhandapani et al, 2020;Faccoli & Favaro, 2016;Pedlar et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation